MicroRNA-221/222 Inhibits the Radiation-Induced Invasiveness and Promotes the Radiosensitivity of Malignant Meningioma Cells - Zhang, Qing; Song, Lai-Rong; Huo, Xu-Lei; Wang, Liang; Zhang, Guo-Bin; Hao, Shu-Yu; Jia, Hai-Wei; Kong, Chui-Lin; Jia, Wang; Wu, Zhen; Xu, Bai-Nan; Jia, Gui-Jun; et al. (Frontiers in Oncology, 2020)
The controversy of adjuvant radiotherapy of meningiomas is at least partially due to the insufficient understanding on meningioma cells’ response to irradiation and the shortage of radiosensitivity-promotion methods. MicroRNA-221 and microRNA-222 were identified as critical regulators of radiosensitivity in several other tumors. However, their effect in meningiomas has yet to be confirmed. Therefore, the malignant meningioma IOMM-Lee cells were adopted, transfected with microRNA-221/222 mimics or inhibitors and irradiated with different dosages. The effects of radiation and microRNA-221/222 were then assessed in vitro and in vivo. Radiation dose increases and microRNA-221/222 downregulation synergistically inhibited cell proliferation and colony formation, prevented xenograft tumor progression and promoted apoptosis, but antagonistically regulated cell invasiveness. Pairwise comparisons revealed that only high-dose radiations (6 Gy and 8 Gy) can significantly promote cell invasiveness in comparison with unirradiated counterparts. Further comparisons exhibited that downregulating the microRNA-221/222 expression can reverse this radiation-induced cell invasiveness to a level of untransfected and unirradiated cells only if cells were irradiated with no more than 6 Gy. In addition, this approach can promote IOMM-Lee’s radiosensitivity. Meanwhile, we also detected that the dose rate of irradiation affects cell cycle distribution and cell apoptosis of IOMM-Lee. A high dose rate irradiation induces G0/G1 cell cycle arrest and apoptosis-promoting effect. Therefore, for malignant meningiomas, high-dose irradiation can facilitate cell invasiveness significantly. Downregulating the microRNA-221/222 level can reverse the radiation-induced cell invasiveness while enhancing the apoptosis-promoting and proliferation-inhibiting effects of radiation and promoting cell radiosensitivity.